Sustainable corporate governance in the United Kingdom: Environmental sustainability in directors' decision-making - Constantin Jung (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2022)
Environmental sustainability is one of the greatest challenges of this century. It depends on both compliance with environmental protection laws and its integration into directors' decision-making beyond these laws. In this regard, the duty to promote the company's success stipulates in the Companies Act 2006 that directors, who are protected by Business Judgment Rule, shall consider their companies' environmental impacts. Since the stakeholders' interests are regarded as a means to increase shareholder value, directors may pursue their companies' environmental sustainability through a business case. The latest changes to the UK Corporate Governance Code 2018 further encourage directors to consider environmental sustainability in their business decisions. They may also link environmental sustainability to mandatory and voluntary disclosures through publishing their companies' achievements. As a result, directors have broad discretion to pursue environmental sustainability beyond environmental protection laws. However, evidence shows that directors frequently neglect this discretion, the environmental sustainability's resulting business case and that they even cause environmental damages to increase (the short-term) shareholder value. This is due to the social norm of shareholder primacy, which is now exacerbated by Brexit's and the Ukraine war's unclear economic impacts as well as the ongoing COVID-19 pandemic. In this regard, the current approach of the UK's company law in the predominant form of narrative reporting laws is insufficient because of the resulting greenwashing possibilities. This paper's main argument is thus that changes to the current legal framework for directors' decision-making are needed to achieve more environmental sustainability. Accordingly, a new principle for the UK Corporate Governance Code 2018 could lead to a greater consideration of environmental sustainability in directors' decision-making and increased shareholder value in times of rising societal awareness of climate change and a growing trend towards environmental activist shareholders. – – Ökologische Nachhaltigkeit ist eine der größten Herausforderungen dieses Jahrhunderts. Sie hängt sowohl von der Einhaltung von Umweltschutzgesetzen als auch von ihrer Einbeziehung in die Entscheidungsfindung von 'Directors' über Umweltschutzgesetze hinaus ab. In diesem Zusammenhang schreibt die Pflicht aus Section 172 im UK Companies Act 2006 Nachfolgendes vor: 'A director (...) must act in the way he considers, in good faith, would be most likely to promote the success of the company for the benefit of its members as a whole, and in doing so have regard (amongst other matters) to (...) the impact of the company's operations on the community and the environment', wobei 'Directors' durch die Business Judgement Rule geschützt sind. Da die Verfolgung von Stakeholderinteressen als ein Mittel zur Steigerung des Shareholder Value angesehen wird, können 'Directors' die ökologische Nachhaltigkeit ihrer Unternehmen durch einen Business Case fördern. Die jüngsten Änderungen des UK Corporate Governance Code 2018 unterstützen 'Directors' zudem noch stärker, ökologische Nachhaltigkeit in ihren unternehmerischen Entscheidungen zu berücksichtigen. 'Directors' können zudem auch ökologische Nachhaltigkeit mit obligatorischen und freiwilligen Offenlegungen verknüpfen, indem sie die positiven Beiträge ihrer Unternehmen zur ökologischen Nachhaltigkeit veröffentlichen. Daher verfügen 'Directors' über einen breiten Ermessensspielraum, um ökologische Nachhaltigkeit über Umweltschutzgesetze hinaus zu fördern. Es zeigt sich jedoch, dass 'Directors' ihren Ermessensspielraum sowie den aus ökologischer Nachhaltigkeit resultierenden Business Case häufig vernachlässigen und sogar Umweltschäden verursachen, um den (kurzfristigen) Shareholder Value zu steigern. 'Shareholder Primacy' ist dafür verantwortlich und wird nun durch die unklaren wirtschaftlichen Auswirkungen des Brexit und des Kriegs in der Ukraine sowie durch die anhaltende COVID-19-Pandemie noch verschärft. Folglich ist der derzeitige gesellschaftsrechtliche Ansatz des Vereinigten Königreichs, ökologische Nachhaltigkeit primär durch Gesetze zu fördern, die narrative Berichterstattung erfordern, nicht ausreichend aufgrund der aus dem narrativen Spielraum resultierenden Greenwashing-Möglichkeiten. Das Hauptargument dieses Papers ist daher, dass Änderungen am derzeitigen Rechtsrahmen für die Entscheidungsfindung von 'Directors' erforderlich sind, um mehr ökologische Nachhaltigkeit zu erreichen. Dementsprechend könnte der UK Corporate Governance Code 2018 in Form eines neuen 'Principle' ergänzt werden. Dies könnte zu einer stärkeren Berücksichtigung von ökologischer Nachhaltigkeit bei der Entscheidungsfindung von 'Directors' und zu einer Steigerung des Shareholder Value in Zeiten eines steigenden gesellschaftlichen Bewusstseins für den Klimawandel und eines wachsenden Trends zu sogenannten 'environmental Activist Shareholders' führen.
urn:nbn:de:bsz:946-opus4-64982
Keywords: 340